The Influence of Family Knowledge About Healthy Homes on the Prevention of ISPA in the Working Area of Sitopeng Health Center in Cirebon City - Hediyana Yusuf; Rina Hardiana; Thia Oktiany (Jurnal Kesehatan Mahardika, 2021)
Healthy home is a place for take a shelter, ensconce and a place for take a rest so that can grow up a perfect life which includes physically, spiritually and socially. Acute respiratory infections (ISPA) is the main cause of morbidity and mortality from infectious disease in the world. This study purpose to determine the effect of family knowledge about healthy homes to disease prevention of ISPA in the Sitopeng public health center working area, Cirebon City.This research method uses analytic survey with cross-sectional research designs. The population is the head of family in the Sitopeng public health center working area at Cirebon City and the total sample is 100 people. The technique of sampling uses Proportionate stratified random sampling (random stratification technique). The instruments for both variable use questionnaire sheet. The analysis for data uses Chi-Square test with significance value α = 0.05. The result of bivariate analysis with Chi- Square test show p-value 0.000 < 0.05, so H0 was rejected, it’s mean that there was an influence of family knowledge about healthy home on the prevention of ISPA in the Sitopeng public health center working area at Cirebon City.